Lord Byron and Dionisios Solomos: Searching for the ‘Before’ and ‘After’ of a Poetical Dialogue - Spinoula, Barbara (Ariadne, 2026)
An interesting poetical dialogue is confirmed when Dionisios Solomos in his notes to the Hymn to Liberty reveals that in composing the scene of the beautiful Greek women dancing, their breasts preparing “milk of bravery and freedom” (stanzas 83–86), he has in mind Lord Byron’s “Isles of Greece” (Don Juan III) and the tears of the Byronic character for the attractive young Greek women dancing, their breasts preparing to breastfeed slaves. This paper endeavours to add to the known echoes of the Byron–Solomos dialogue (resounding in Angelos Sikelianos and Costas Varnalis) fragments that—to the best of my knowledge—have not been discussed by critics: it is fragments from Solomos’s “To the death of Lord Byron” and from prose texts by Georgios Tertsetis. Fragments of Andreas Calvos’s Odes are also studied, along with the Graces, by the preeminent poet in Italy, Ugo Foscolo. The Graces were inspired by the complex of Antonio Canova and constitute a possible common literary memory which is recalled by Calvos, Solomos and even Byron. Not only the similar image, but mainly the similar words chosen in the four poets’ description of the young dancers encourage such an assumption.